THE USE OF ADDRESS FORM IN HITCH MOVIE: A SOCIOLINGUISTIC STUDY - Abdul Khalik (English Department, Faculty of Humanities, Andalas University, 2012)
This article discusses the address forms used in a conversation. The study is aimed at explaining the background of the use of address forms and social dimension which is reflected from the use of the address forms in the interaction. The data are taken from a movie entitled